Glitter in a 2D monolayer1. Issue 39 (21st October 2015) - Yang, Li-Ming; Dornfeld, Matthew; Frauenheim, Thomas; Ganz, Eric
<x xml:space="preserve">Abstract</x> We predict a highly stable and robust atomically thin gold monolayer with a hexagonal close packed lattice stabilized by strong relativistic effects and aurophilic attractions with maximum number of Au–Au bonds in the 2D plane.